Proses Penyidikan oleh Kepolisian Terhadap Tindak Pidana Perdagangan Orang dalam Aplikasi Whatsapp (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
To understand the investigation into the crime of trafficking in persons on Whatsapp media and understand the obstacles in police investigations of social media such as WhatsApp. This research uses case studies, namely examining cases and taking data directly on the parties involved in the chance to be investigated. In this study, it was found that the perpetrators of the crime of trafficking in persons did so because of economic problems, and victims of the crime of trafficking in persons were forced to do so because they were entangled in the deceit of the perpetrators, the victim who was a good friend of the victim was deceived and ensnared so that he needed to undergo rehabilitation for the perpetrator's actions. Social media, such as Whatsapp, is a crime that is difficult to trace because the perpetrators of crimes can be outside the jurisdiction of the Pekanbaru Police, but successful investigations and investigations have been carried out due to reports and assistance from public information cooperation. Around and feel disturbed by this criminal act of trafficking in persons. The most common obstacles encountered in these investigative cases include internal barriers consisting of limited jurisdiction areas and cyber mastery constraints. Second, there are external constraints (investigations into victims and lack of public legal concern).